Certain geometric properties define on meromorphic via Bernardi integral operator on complex Hardy space - Omar j. mohammed; Abdul Rahman S. juma (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2026)
The aim goal of this paper to study the bernardi integral operator on a new sub class of analytic meromorphic function of Hilbert space and more specifically on the hardy space , and we obtain the coefficient estimates for the new subclass with certain geometric properties as growth and distortion also discussed radii of starlikeness and convexity functions in the end the convexity of linear combination with the class is discussed.